Conditional Process Model the Influence of Personality Traits and Behavioral Bias on Perception of Investment Performance - Muhammad Yusuf; Nugraha Nugraha; Disman Disman; Toni Heryana; Maya Sari (Journal of International Conference Proceedings, 2021)
This study examines the influence of personality traits on perceptions of investment performance with behavioral bias as a mediation and demographic factor as a moderation in the Indonesian capital market. Perception of investment performance is dependent variable in this study. While personality traits are independent variable in this study. Bias overconfidence as a mediating variable and demographic factor as a moderating variable. The research data processing uses the conditional process model. The results show that demographic factor is proven to be effective in moderating the influence of personality traits on perception of investment performance by mediating behavioral bias.